Intake and feeding efficiency in feed-lot lambs Consumo e Eficiência Alimentar em Cordeiros Confinados - Joadil Gonçalves Abreu; Joanis Tilemahos Zervoudakis; José Walter Santos; Luciano da Silva Cabral; Alexandre Lima Souza; Rosane Cláudia Rodrigues (Revista Brasileira de Saúde e Produção Animal, 2008)
The present experiment was carried out in order to evaluate the intake and feed efficiency in fed-lot sheep as function of the body weight (BW) variation. Data from three experiments with 50 feedlot lambs maintained in individual metabolic cages and fed diets composed of 50:50 roughage:concentrate were used. The experiment lasted 120 days; every 21 days the animals were weighed and the dry matter intake and body weight change were daily done. The intake was determined by checking daily the feed offer level and orts. The increased in animals body weight incremented the dry matter intake in 30.8g/kg of body weight/day, but promoted reduction of 0.0318% when the intake was expressed as percentage of BW. In addition, the advance of body weight affected negatively the feed conversion (FC), where animals with BW of 30 kg showed estimated FC of 4.55 of dry matter/kg of BW gain, while animals with BW of 45 kg have would food conversion of 7.03 kg of DM/kg of BW gain. Este trabalho foi realizado com o objetivo de avaliar o consumo e a eficiência alimentar em ovinos confinados em função da variação no peso vivo (PV). Foram utilizados dados de três experimentos com cordeiros em confinamento, 50 animais no total, mantidos em gaiolas individuais para estudos de metabolismo, alimentados com dietas de relação volumoso: concentrado 50:50. Durante o experimento (120 dias), os animais foram monitorados quanto ao consumo diário de matéria seca e à variação de peso vivo, por meio de pesagens realizadas a cada 21 dias. O consumo foi determinado pelo monitoramento diário da oferta de alimento e das sobras. Com o do peso vivo dos animais aumentou o consumo de matéria seca em 29,38g/kg de PV/dia, mas promoveu redução de 0,0318% quando expresso em porcentagem do PV. Além disso, o avanço do PV afetou negativamente a conversão alimentar (CA), de modo que animais com 30kg de PV apresentaram CA estimada de 4,55kg de MS/kg de PV ganho, enquanto animais com peso vivo de 45 kg apresentariam CA de 7,03kg de MS/kg de peso vivo ganho.